How Can Money Conquer France? On the Question about the Monetary Policy of King Henry V in 1415–1422 - Oleg Igorevich Nuzhdin (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2020)
This article studies the peculiarities of the monetary policy of English king Henry V in the territories of the Kingdom of France occupied by him between 1415 and 1422. The purpose of the study is to establish its influence on the state of finance in France and, first of all, on the sharp depreciation of silver money following the defeat. Within the framework of English politics, two stages can be clearly traced: the first one lasted from 1415 to 1420, when monetary policy was indirect in nature, influencing the French economy by the fact of conquest and becoming an additional factor in the aggravation of the domestic political struggle, and the other one lasted from 1420 to 1422 and was connected with the intention of Henry V as regent of the Kingdom of France, to bring the financial system into relative order. The author refers to French and English chronicles, The Diary of a Parisian Citizen, as well as the ordinances of the kings of France, which reflected the peculiarities of the monetary policy, more particularly, changes in the exchange rate and weight of silver coins and attempts to carry out reforms. The study carried out makes it possible to find out that the depreciation of the French silver coin was associated with the beginning of the British conquest of Normandy and the transfer of mints located there. A sharp drop in the money rate occurred after the transfer of Paris into the hands of the Burgundians and the formation in the fall of 1418 of an independent financial administration in the south of France under the control of the dauphin. On the contrary, some stabilisation followed the conclusion of the Treaty of Troyes, and the General States adopted a course towards reforms in December 1420. The author determines the stages of the reform and the reasons for its delay. These include: the lack of control over all the mints of the kingdom, the lack of coin metal and the required number of qualified personnel. Finally, the premature death of Henry V in the summer of 1422 did not allow the completion of the monetary reform.